Variabilidade genética e variação estacional de 'Candidatus Liberibacter asiaticus' em citros no Paraná - Sauer, Aline Vanessa (2014)
Huanglongbing stands out as the most important disease of citrus worldwide. The absence of genetic materials resistant makes its management difficult and costly. Thus, the aim of this study was to evaluate the variability among isolates closely related, monitor the population of 'Ca. Liberibacter asiaticus' in citrus plants in northwestern Paraná, and validate a method for direct extraction of DNA for real time PCR detection. The variability study was conducted in citrus plants in an experimental orchard (Maringá-PR) through the use of microsatellite regions associated with Simple Sequence Repeats (SSR) of the bacterium. Seasonal variation of the bacterial population was studied in citrus seedlings maintained in a greenhouse, in sweet orange plants in an experimental orchard, and Tahiti acid lime plants in a commercial orchard in Maringá, Paraná State, and still, sweet orange plants in a commercial orchard in Paranavaí, Paraná. The bacterial population was monitored by real-time PCR by collecting monthly symptomatic leaves from the detection of the bacterium in the plant. The methods of sample preparation were directly performed with detection protocol real-time PCR using TaqMan® probe. The population genetic structure was determined by including 21 haplotypes, grouped into three main groups. The research revealed that genetic diversity is present in the area since the beginning of the manifestation of HLB. There were significant differences in Ct (Cycle Threshold) in samples collected in different seasons, and autumn was the best time for detection of bacteria in plants in the field. The direct extraction method was validated and efficient to detect 'Ca. Liberibacter asiaticus', showing similar agreement with samples whose DNA purification was performed.